Structure and function of the PHO82-pho4 locus controlling the synthesis of repressible acid phosphatase of Saccharomyces cerevisiae. - Toh-e, A (1981)
pho4 mutants of Saccharomyces cerevisiae, although rare among phosphatase-negative mutants isolated from wild-type strains, were isolated efficiently from pho80, pho85, or pho80 pho85 strains. The distribution of these pho4 mutants over the pho4 locus was determined by analyzing random spores of two- and three-factor crosses. The pho4-4 mutation confers temperature-sensitive synthesis of repressible acid phosphatase. An intragenic suppressor for the pho4-12 allele results in the temperature-sensitive synthesis of repressible acid phosphatase. Recombination between these sites occurs at 1.0 to 3.0%, the highest for any pair of sites within the pho4 locus. All these results strongly indicate that the information of the pho4 locus is translated into a protein. The PHO82 site was mapped inside the pho4 locus by random spore analysis. The order met10-pho4-1PHO82-1-pho4-9 on the right arm of chromosome VI was confirmed by tetrad analysis. Doubly heterozygous diploids, pho3 PHO82c PHO4+/pho3 pho82+ pho4, produce variable amounts of repressible acid phosphatase under repressive conditions depending on the combination of PHO82c and pho4 alleles. This phenomenon may reflect the constitutive production of the pho82+-pho4 product in the repressed condition, which interferes with the function of the PHO82c-PHO4+ product. The earlier model for the function of the PHO82-pho4 cluster, in which the PHO82 site acts as an operator of the pho4 gene, has been revised to a model in which the PHO82 site codes for the part of the pho4 protein that has affinity for the regulatory protein encoded by the pho80 and pho85 genes.